1993
DOI: 10.1159/000187362
|View full text |Cite
|
Sign up to set email alerts
|

Renal Scarring Is Enhanced by Phorbol Myristate Acetate following Infection with Bacteria with Mannose-Sensitive Pili

Abstract: Renal scarring is considered to develop in the later stages of chronic pyelonephritis. In our experimental model of pyelonephritis, bacteria with mannose-sensitive (MS) pili on their surface promoted renal scarring following inoculation into the renal parenchyma. The administration of cyclophosphamide to induce leukopenia and of superoxide dismutase to inactivate superoxide released from polymorphonuclear leukocytes (PMN) at the infection site suppressed any renal scarring following the infection. Conversely, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This leads to a brisk migration of inflammatory cells such as polymorphonuclear leukocytes (PMN) and macrophages to the site of infection [26,27]. In fact, both macrophages and neutrophils may liberate a variety of cytokines, metabolites of arachidonic acid, and noxious inflammatory mediators such as oxygen radicals and lysosomal enzymes during the process of phagocytosis, which also may account for the deleterious effects to host cells, including tissue damage and scar formation [27][28][29][30]. By then, macroscopic and microscopic examinations demonstrate abscess formation with corresponding focal suppurative necrosis of kidney structures [21,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to a brisk migration of inflammatory cells such as polymorphonuclear leukocytes (PMN) and macrophages to the site of infection [26,27]. In fact, both macrophages and neutrophils may liberate a variety of cytokines, metabolites of arachidonic acid, and noxious inflammatory mediators such as oxygen radicals and lysosomal enzymes during the process of phagocytosis, which also may account for the deleterious effects to host cells, including tissue damage and scar formation [27][28][29][30]. By then, macroscopic and microscopic examinations demonstrate abscess formation with corresponding focal suppurative necrosis of kidney structures [21,26].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of acute inflammation in experimental models by cyclophosphamide-induced neutropenia [29], antioxidant therapy with superoxide scavengers such as superoxide dismutase [33], ascorbic acid and ebselen [34], and even complement depletion with cobra venom factor [35] have all been reported to reduce kidney damage after infection. Other studies with oxytocin [28], melatonin [24,27], pentoxifylline [36], vitamin A [37], and montelukast [30] (a selective leukotriene CyslT1 receptor antagonist) showed the same result.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the pathogenicity of the hyphal form is thought to be marked [7][8][9][10][11], although this has not yet been clari fied by any experimental study reported in the literature. In addition, although the leukocytes appearing at sites of inflammation in bacterial [12,13] as well as Candida infections [14] exert a bacterio-and fungicidal action as part of the host's defense mechanism, the oxygen radicals generated at the same time in association with the respira tory burst of leukocytes may induce tissue injury [15,16]. However, few reports are available on oxidant injury in renal tissue in pyelonephritis [17] and none on oxidant injury in Candida pyelonephritis.…”
Section: Introductionmentioning
confidence: 99%